Application of ISSR marker in pharmacognosy: current update - Kurane, Jayvant; Shinde, Vaibhav; Harsulkar, Abhay (Pharmacognosy Reviews)
ISSR (Inter Simple Sequence Repeat) is one of the popular techniques of DNA fingerprinting because of several reasons. In many fields, ISSR markers have proved their utility. There are many applications of ISSR in various aspects of medicinal plants. ISSR based markers have utility in the fields like genetics, taxonomy, physiology, embryology etc. and recently the ISSR based markers have found wide applicability in pharmacognostic characterization of medicinal plants. As use of herbal medicines is increasing, there is urgent need of newer technologies and its proper application. In recent years, pharmacognosy has witnessed advent of such new technologies. This review provides detail list of plants, which are studied by ISSR marker and discuss some of the important application in medicinal plant research.
Keywords: ISSR; molecular marker; genotyping; genetic diversity; authentication